The Dark Side of Medical Staff: How Dark Traits Lead to Work Burnout - Zeinab Zaremohzzabieh; Ruqia Safdar Bajwa; Haslinda Abdullah; Huma Batool (Media Kesehatan Masyarakat Indonesia, 2025)
The dark side of personality has begun to be studied extensively in the fields of social, personality, and organizational psychology in recent years but little is known about which of the Dark Triad traits is more malevolent in organizational context. Therefore, the present study aims to investigate the effects of dark triad traits on counterproductive work behavior along with the mediating role of burnout. A cross-sectional survey was used to collect data from 208 permanent employees of medical hospitals. A personality-based research model was proposed to test the hypothesis. The questionnaire consisted of a dark triad scale, a counterproductive work behavior scale, and a burnout scale. Different statistical techniques, i.e., correlation, and regression were applied to test the direct effects, and the PROCESS-macro method was applied to test indirect effects (mediation). The findings of the study revealed that dark triad traits and counterproductive work behaviors are significantly correlated (p<0.05). Narcissism is a significant predictor of counterproductive work behavior as compared to Machiavellianism and psychopaths (R2= 0.23). Furthermore, findings reveal that emotional exhaustion significantly mediates the relationship between dark triad and counterproductive work behavior (R2 = 0.66). Policymakers and higher management of public sector institutions especially focus on psychological health and organizational climate to reduce the workplace’s harmful behaviors. Finally, this study theoretically enhances knowledge of personality psychology literature by explaining the negative consequences of negative personalities in the workplace.